The Metro City Election Anomaly: The Incumbent's Failure and the Challenger's Victory - Retno Sari, Lisa; Resmalasari, Septiani; Iswara Pangastuti, Era (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Jurai Siwo Lampung, 2025)
Local elections (Pilkada) are an important moment in local democracy, often pitting incumbents against their rivals. However, not all incumbents are able to retain their seats. This study examines the defeat of the incumbent Mayor of Metro in the 2024 Metro local elections. Incumbents in several democratic elections in Indonesia often have a high re-election rate and a good chance of winning the contest. The opposite phenomenon occurred in Metro City, Lampung, where the incumbent, despite successfully becoming a candidate and being supported by the majority of political parties, failed to secure victory, even suffering defeats in all district-level electoral districts. This research uses a qualitative approach, with data collection methods including interviews, observations, and literature reviews. Data analysis was conducted using qualitative data analysis with the stages of reduction, presentation, and conclusion drawing. The results of the study indicate that there are several factors contributing to the incumbent's failure in the 2024 Metro Mayor Election. First, the educational level of city residents influences their tendencies and satisfaction with the incumbent's performance. Second, public dissatisfaction with the incumbent's leadership. Third, the existing political party machinery was not optimally supporting the incumbent's re-election. Fourth, social media and digital literacy among city residents in responding to campaigns in the digital space.